Delovni čas in letni dopust z vidika standardov MOD, MESL in novejše sodne prakse Sodišča EU - Senčur Peček, Darja (Delavci in delodajalci, 2019)
The article deals with some selected issues related to working time (its duration and distribution, definition, etc.) and the annual leave. It presents the minimal standards deriving from ILO Conventions, as well as from the European Social Charter and EU Law, as interpreted by the supervisory authorities and EU Court. In this light, the Slovenian regulation of working hours and annual leave, as well as the problems that appear in practice and in the case law are being addressed.
Keywords: annual leave; delovni čas; European Court; European Social Charter; Evropska socialna listina; ILO; letni dopust; MOD; nadurno delo; Sodišče EU; working hours